Fostering Patriotism Through Unity: Implementation of Pancasila's Third Principle in Elementary Character Education - Yuliana, Nana Pirda; Idris, Muhamad; Irawan, David Budi (Journal of Innovation and Research in Primary Education, 2025)
In Indonesia's diverse society, implementing Pancasila's third principle—"Persatuan Indonesia" (Unity of Indonesia)—is crucial for fostering patriotism among elementary students. Despite formal curriculum inclusion, challenges persist in effectively translating abstract unity values into meaningful learning experiences. This study investigated how the third principle of Pancasila is implemented to foster patriotism among fourth-grade students in classroom settings. A qualitative descriptive case study was conducted at SD Negeri 68 Palembang involving 30 fourth-grade students and one homeroom teacher. Data were collected through systematic classroom observations, semi-structured interviews, and document analysis over three months (October-December 2024). Data analysis followed the Miles and Huberman framework, incorporating data reduction, display, and conclusion drawing with triangulation to ensure credibility. Findings revealed high frequencies of collaborative behaviors aligned with unity principles, including active cooperation (91.7%), respectful communication (87.5%), and inclusive participation (79.2%). Student interviews demonstrated strong comprehension of unity concepts, with 93.3% understanding unity as cooperation and 90% expressing shared national identity. The teacher employed systematic pedagogical strategies integrating character education with academic content through storytelling, democratic conflict resolution, and experiential learning activities. However, 20% of students exhibited passive engagement patterns, indicating need for differentiated instructional approaches. Results align with social cognitive theory and support democratic patriotism development rather than blind conformity. The study confirms the effectiveness of teacher-led character education when combined with systematic classroom practices. Findings contribute to character education literature by providing empirical evidence of successful Pancasila implementation and practical frameworks for educators seeking to enhance patriotic attitude development among elementary students.